A comprehensive review of recent studies on pharmacokinetics of traditional Chinese medicines (2014–2017) and perspectives. (3rd April 2018) - Shi, Peiying; Lin, Xinhua; Yao, Hong
Abstract: Traditional Chinese medicines (TCMs) have a long history for safely treating human diseases. Unlike western medicine, TCMs usually contain multiple components synergistically and holistically acting on the diseases. It remains a big challenge to represent rationally the in vivo process of multiple components of TCMs for understanding the relationship between administration and therapeutic effects. For years, efforts were always made to face the challenge, and the achievements were obvious. Here, we give an comprehensive overview of the recent investigation progress (from 2015 to 2017, except the part of 'integrated pharmacokinetics of TCMs' from 2014 to 2017 and the part of 'reverse pharmacokinetics in drug discovery from natural medicines' in 2014) on pharmacokinetics of TCMs, mainly referring to the following six aspects: (1) classical pharmacokinetic studies on TCMs; (2) absorbed components and metabolites identification of TCMs; (3) pharmacokinetic herb–drug interactions and herb–herb interactions with TCMs; (4) integrated pharmacokinetics of TCMs; (5) pharmacokinetic and pharmacodynamic combination studies to dissect the action mechanisms of TCMs; and (6) reverse pharmacokinetics in drug discovery from natural medicines. Finally, based on the insights from the recent progress and our latest efforts, we propose new perspectives on the integrated pharmacokinetics of TCMs.